IMPLEMENTASI METODE FUZZY SUGENO PADA ROBOT KAPAL PENGHINDAR RINTANGAN - Sarmayanta Sembiring; Rossi Passarella; Hendra Setiawan; Yandi Prasetia (Annual Research Seminar (ARS), 2015)
This research was designed a control fuzzy system using Sugeno method for obstacle avoidance behavior on a ship robot. Ultrasonic sensor (SRF05) is applied as input sensor for detecting and measuring a distance of obstacles. This single sensor is setting with 3 zone area which area zone 600, zone 900 and zone 1200. The sensor is controlling by servo motor more over this output of sensor is using as input data for fuzzy Sugeno which is processed in microcontroller. The microcontroller is sending the output result from fuzzy Sugeno to a servo motor which is then controlling the driving rudder. The experiment result show the sensor is covering the distance of 10 cm to 200 cm for 3 zones respectively the maneuver of ship robot is able to move freely without colliding due to maximum error of angle of rudder is 3,684%